CRIMINALIZATION OF FRAUD CRIMES IN CAPITAL MARKET TRANSACTIONS - Ambarwati, Mega Dewi (YURIS: Journal of Court and Justice, 2022)
As an economic instrument, capital market is not free from certain parties abuse to enrich themselves and it against the law. Crimes in the capital market sector are complex and difficult to prove, let alone being brought before a court, given the nature of the market which is very sensitive to material facts (news related to the course of judicial process) in the form of information related to the capital market. Crimes of capital market sector are complex and difficult to prove, especially being brought before a court, within the characteristic of the market which is very sensitive to material facts (related to the course of judicial process) in form of information related to the capital market. The objective of developing capital market as the basis for sustainable development plan is to increase economic growth and income distribution, to develop an economy that is globally oriented related to the advances in science and technology for the prosperity of the people. The purpose of this study is to find out how government's role as an effort to avoid fraud in the capital market is detrimental to investors. The research method used statutory approach and conceptual approach. Based on the results and discussion in the study, it can be concluded that, the adoption of the division of offenses into two types, namely capital market crime offenses and capital market offenses, shows that the Investment Law follows the provisions contained in the Criminal Code which are laws (general provisions).